Scrabble Board Game as a Learning Tool for Improving Arabic Vocabulary Based on Experiential Learning - Agus Yasin; Khansa Nabila; Alif Cahya Setiyadi (Institut Agama Islam Negeri Curup, 2026)
This study aims to develop a Scrabble Board Game based on Experiential Learning principles to improve Arabic vocabulary mastery among beginner-level students. The research employed a quantitative Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through expert validation questionnaires, vocabulary pre-test and post-test instruments, classroom observations, and interviews. Media validity was examined through content and construct validation by three experts: an Arabic language expert, a learning media expert, and a teaching practitioner using a Likert-scale assessment, while instrument reliability was ensured through expert judgment. The implementation involved 20 second-grade students at Madrasah Ibtidaiyyah over three learning sessions. Quantitative data were analyzed using descriptive statistics, N-Gain analysis, and a paired-sample t-test, supported by descriptive qualitative analysis. The results showed a significant improvement in students’ Arabic vocabulary mastery, with the average score increasing from 54.3 to 82.1 and an N-Gain score of 0.61, indicating moderate to high effectiveness. At the same time, the paired-sample t-test confirmed statistical significance (p < 0.001). This study concludes that integrating a Scrabble Board Game with Experiential Learning effectively enhances Arabic vocabulary acquisition and student engagement.